Bibliometric analysis of hotspots in Staphylococcus aureus drug resistance research - Jianguo Shi (Frontiers in Microbiology)
ObjectiveBibliometric analysis was used to visualize the current literature data on Staphylococcus aureus drug resistance.MethodsWe used a bibliometrix package that utilizes R 4.4.1, all S. aureus drug resistance related research literature in the WOS core database, and data visualization and analysis of the retrieved research literature.ResultsA total of 3,253 research articles on Staphylococcus aureus resistance were screened, and the number of publications related to Staphylococcus aureus resistance is increasing year by year. China ranks first in the number of publications, and the United States ranks first in terms of citations. Frontiers in microbiology has published the most articles on this research topic. Wang Y, Lee JH, and Simoes M have published the most articles, and Franci G has the most citations. The Egyptian Knowledge Bank (EKB), the Chinese Academy of Sciences, and Harvard University are the main research institutes. A total of 15,824 authors have contributed to the field, with the majority of authors coming from China, followed by South Korea and the United States, and most of them coming from the Chinese Academy of Science and Jilin University. The mechanism of drug resistance in Staphylococcus aureus was the most important research hotspot, with Staphylococcus aureus coming up 984 times, (10%), followed by antibiotic-resistance (693 times, 7%) and biofilm formation (517 times, 5%).ConclusionThis study comprehensively summarizes past research trends in Staphylococcus aureus resistance and identifies the countries, institutions, authors, journals, and publications involved in this field. The results provide a comprehensive overview of the study of resistance in Staphylococcus aureus.